The Asian Cohort for Alzheimer's Disease (ACAD) Pilot Study. (20th December 2022) - Wang, Li‐San; Ho, Pei‐Chuan; Tee, Boon Lead; Li, Clara; Gu, Yian; Yokoyama, Jennifer S.; Vardarajan, Badri N.; Reyes‐Dumeyer, Dolly; Faber, Kelley M.; Lee, Wan‐Ping; Tzuang, Marian; Choi, Yun‐Beom; et al.
Abstract: Background: Asian Americans and Canadians (ASACs) are the fastest growing minority group in the US and Canada. ASACs are under‐sampled in Alzheimer's disease (AD) research. Culturally appropriate, community‐based approaches to recruit these understudied communities are urgently needed, and in 2021 the Asian Cohort for Alzheimer's Disease (ACAD) began recruitment to the first large dementia genetics cohort to examine genetic and non‐genetic risk factors for AD among ASACs. Our clinical and community‐based participatory research (CPBR) scientists have a long collaborative history and specific experience in leading AD and CBPR research. Method: The ACAD pilot study has 8 recruiting sites (6 US and 2 Canadian), a coordinating site, and an analysis site. ACAD piloted a data collection packet (DCP) and pre‐screening/sample collection procedures. The Outreach workgroup translated the forms and an outreach campaign into Chinese (Mandarin and Cantonese), Vietnamese and Korean. Data Management created a central RedCap database. The Training workgroup developed a curriculum for the administration of the DCP and for culturally appropriate approaches to recruitment. We recruited in collaboration with community partners, clinics, and nursing homes that serve Asian communities. Result: ACAD's pilot study has consented 216 participants (142 Chinese, 20 Vietnamese and 54 Korean), and 126 (58%) have completed the DCP. The majority the consent (64.3%) were given by women. The age range of the sample is 60‐93 years. 60.3% have college or graduate level education. 101 of the 126 participants provided saliva (51) or blood (50) biosamples. Data entry is complete, with Consensus Diagnoses fully reviewed on 18 participants. Among 34 diagnosed participants, there are 19 healthy controls, 11 Subjective Cognitive Complaints, 3 Mild Cognitive Impairments, and 1 Probable or Possible AD case. Conclusion: Lessons learned during the pilot phase of ACAD will provide guidance for future studies to explore risk factors for AD and related dementias. In collaboration with ongoing consortium efforts in Alzheimer's Disease Genetics Consortium (ADGC), insights from ACAD may identify potential novel, population‐specific therapeutic pathways for AD. Our long‐term goal will be to expand ACAD to have a larger sample size and include other Asian American subgroups .